THE ROLE OF AI IN LANGUAGE LEARNING - Mamatqulova Diyonat Shavkat qizi (TADQIQOTLAR, 2025)
Annotation. This article examines the growing role of Artificial Intelligence (AI) in language learning, highlighting its transformative impact on both formal and informal educational contexts. It explores how AI-powered tools—such as language learning apps, chatbots, personalized learning platforms, and machine translation services—are reshaping the way learners acquire and interact with new languages. The study also discusses the benefits of AI, including adaptive learning, real-time feedback, and immersive language environments, while addressing challenges such as over- reliance on technology, privacy concerns, and the potential loss of human interaction. Overall, the article provides a comprehensive overview of how AI is enhancing language acquisition processes and contributing to more accessible and efficient language education worldwide.